Odpowiedź :
Odpowiedź:
W załączniku:)
Szczegółowe wyjaśnienie:
Proszę bardzo! Liczę na naj:)
![Zobacz obrazek Kajanowak08](https://pl-static.z-dn.net/files/dbb/e12b09616814fb615b17a3889260e23a.jpg)
Odpowiedź:
Szczegółowe wyjaśnienie:
3x-3(a-2x)=a+2(a+5x)
3x-3a+6x=a+2a+10x
-3a-2a-a=-3x-6x+10x
-6a=7x /:(-6)
a= -7x/6
Odpowiedź:
W załączniku:)
Szczegółowe wyjaśnienie:
Proszę bardzo! Liczę na naj:)
Odpowiedź:
Szczegółowe wyjaśnienie:
3x-3(a-2x)=a+2(a+5x)
3x-3a+6x=a+2a+10x
-3a-2a-a=-3x-6x+10x
-6a=7x /:(-6)
a= -7x/6